A methodology to estimate NMVOC biogenic emissions: sensitivity analysis and first application in Lombardy. (1st January 2000) - Longoni, Maria Grazia; Maffeis, Giuseppe
This work describes a methodology to estimate NMVOCs from vegetation in the Lombardy region. The proposed method is a "bottom-up" one: starting from local data, at a municipality level, emissions have been estimated across Lombardy. By changing the different land use species assignment and the other site-specific inputs, it is possible to apply this methodology to any area. Two NMVOC pollutants have been considered: isoprene and monoterpenes. Their emissions have been computed using both Tingey, modified by Pierce, and Guenther algorithms. Isoprene and monoterpene emissions reach their highest values during the summer when the temperature, solar radiation and the foliage biomass are at a maximum. In the Lombardy region, the isoprene and monoterpenes estimate is about 200 tons/day; the CORINAIR '90 estimate is about 50 tons/day. Unfortunately the most sensitive input data, i.e. the emission rates and the biomass factors, are the ones with the highest uncertainty.